The Relationship between Family Support and Elderly Behavior in Hypertension Control - Khairiah Putri; Bety Agustina Rahayu (Indonesian Journal of Nursing and Health Sciences, 2023)
The elderly are the age group most vulnerable to suffering from hypertension. Hypertension is a disease that cannot be cured but must always be controlled or controlled so as not to experience complications. Hypertension control behavior is the main thing to prevent complications from occurring. Efforts to control hypertension that can be done are by regulating a good diet, avoiding caffeinated drinks, cigarettes, and alcoholic drinks, doing light exercise, meeting the needs of rest by sleeping for 6-8 hours per day, controlling stress and family support can play a role in making the elderly behave healthily and help make decisions for the elderly with hypertension. The purpose of this study was to determine the relationship between family support and elderly behavior in controlling hypertension at Posyandu Dahlia, Karanganom, Wonokromo, Pleret, Bantul. This type of research is quantitative with correlation descriptive research design. The population in this study amounted to 41 elderly people. Sampling in this study used total sampling techniques and used Kendall's tau statistical tests. Based on the results of Kendall's tau test showed that p value = 0.022 < Î± = 0.05. This shows the relationship between family support and elderly behavior in controlling hypertension at Posyandu Dahlia, Karanganom, Wonokromo, Pleret, Bantul. Most received sufficient family support, as many as 19 elderly (46.3%) and the behavior of the elderly with sufficient category that is as much as 16 elderly (39.0%). Conclusion is a relationship between family support and elderly behavior in controlling hypertension at Posyandu Dahlia, Karanganom, Wonokromo, Pleret, Bantul.